Calculation of structural parameters of a vibratory machine - Gerasymenko , Volodymy; Lus, Volodymyr; Bielykh, Iryna (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article is dedicated to the development of a vibratory machine for compacting concrete mixtures, ensuring the adaptation of vibration modes to the mixture's condition to enhance energy efficiency and concrete quality. The study was conducted through literature analysis, vibration parameter modeling, and calculation of structural characteristics. It was established that modern methods, such as DEM and CFD, highlight the need for flexible vibration control to prevent microstructure defects. A machine design based on elastic pneumatic shells operating in resonant mode is proposed. Key formulas for calculating the vibratory platform are provided. The design achieves a 15% reduction in energy consumption compared to traditional machines, stable compaction, and adaptability to various mixture types. The results confirm the effectiveness of the proposed solution for forming a dense concrete microstructure. Further research involves experimental validation and parameter optimization.
Keywords: vibratory machine; concrete compaction; resonant mode; elastic shells; energy efficiency; concrete quality; concrete mixture